Hubungan Pemahaman Program UKS dan Peran Guru terhadap perilaku hidup sehat di Kecamatan Tandun - Rahmi Fitria; Handayani, Eka Yuli; Junita, Elvira (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2024)
Education and health are interconnected, in school, children need optimal health status to be able to follow lessons and concentrate well. Based on (UU) No. 2 of 1989, it is explained that education is a conscious and planned effort to create a learning atmosphere and teaching and learning process that is appropriate to activate the potential of children who have a spiritual, religious spirit, self-control and health. The aim of this research is to determine the relationship between understanding the UKS program and the role of PAUD teachers on healthy living behavior in Tandun District. The design of this research is a correlation with a cross sectional design. The total sample was 28 people determined using the saturated sampling method. The independent variable is the provision of lavender aromatherapy and the dependent variable is labor pain. The test results obtained a value of p=0.03, meaning there is a significant relationship between UKS's understanding of healthy living behavior and the statistical test results obtained a value of p=0.02, meaning there is a significant relationship between the role of teachers towards healthy living behavior. The conclusion of this research is that understanding UKS and the role of PAUD teachers is significantly related to students' healthy living behavior at school. The role of PAUD teachers in this case includes choosing nutritious food, reminding children to always maintain personal and environmental cleanliness, prohibiting the consumption of dangerous substances such as cigarettes and alcohol, and also reminding and encouraging them to do morning exercise at school.